Myopic shift of clinical refraction following cataract phacoemulsification with IOL implantation in an avitreal eye - E. N. Panteleev; A. N. Bessarabov; V. V. Malyshev (Oftalʹmologiâ, 2014)
Purpose: Propose a correction of IOL power calculation for the cases of cataract phacoemulsification after preceding subtotal vitrectomy.Methods: The study enrolled 32 cases (32 patients) cataract phacoemulsification with IOL implantation after subtotal vitrectomy.Patient age averaged 48±3 years. In all cases, the elastic IOLs were implanted with the value of the constant A from 118.0 to 119.0. Termevaluation of clinical refraction after phacoemulsification surgery was on average 3 months. A retrospective analysis was performed of refractive outcomes using the inverse method of calculation.Results: In a retrospective analysis, the error calculated IOL power by an average of 0.8 D, which leads to a shift in clinical refraction towards myopia. IOL after surgery avitreal eye on the average is closer to the top of the cornea by 0.5 mm, relative to the standard situation. Conclusion: For preoperative IOL power calculations after subtotal vitrectomy A-constant can be modified as follows: Am = A-0.9.